Silício na produtividade e na indução de resistência direta e indireta do sorgo aos pulgões - Lima, Diego Tolentino de (2018)
Silicon (Si) as an inducer of plant resistance against pests and diseases, either by mechanical action, production of chemical compounds or attraction of the third trophic level, is the subject of several of research. The goal of this study was to evaluate the effect of fertilization with Si on productivity and induction of direct and indirect resistance to aphids in sorghum (Sorghum bicolor) culture under greenhouse and field conditions. In a greenhouse, 16 sorghum genotypes were evaluated for the response to Si fertilization, in a completely randomized design, with two fixed factors 16x2 (0 and 261 kg ha-1 of Si), with three replications. Of these genotypes, four responses to Si fertilization were evaluated in the field, with a randomized block design, four replications, and three fixed factors 4x2x3 (4 genotypes x 2 doses, 0 and 400 kg ha-1 of Si, x 3 sowing seasons). The weekly number of aphids and parasitoids in the field, accumulated Si concentration in the leaf, plant height, percentage of lodging and plants attacked by borer (Diatraea saccharalis), severity of anthracnose disease (Colletotrichum sublineolum), yield of grains, fresh and dry mass of sorghum plants produced in the field, were evaluated. In an experiment in the field during the third planting season the attractiveness of parasitoids was evaluated by the number of parasitized aphids. In a greenhouse experiment, the accumulation of Si in the sorghum plant, weight and quantification of the protein in the aphid Schizaphis graminum and in the parasitoid Lysiphlebus testaceipes were evaluated in plants with and without Si. The response of sorghum to Si fertilization under greenhouse conditions varied according to the genotype, and of the 16 genotypes tested, 12 were responsive accumulating more Si when fertilized with this element. Responsive genotypes in a greenhouse were also in the field. However, Si influence on grain yield and fresh and dry mass production in sorghum was not verified, although it reduced the lodging of the plants. In the field, Si fertilization, via soil, promoted the induction of direct resistance in two sorghum genotypes to S. graminum, reducing the average number of aphids per plant. The induction of indirect resistance by silicon in sorghum plants was observed in the field by the greater parasitism of aphids by L. testaceipes in plants fertilized with Si. The resistance induced by Si to anthracnose disease in sorghum was also verified in the field, reducing the severity of this disease. However, the resistance induced by Si to the borer, D. saccharalis, was not verified under the same conditions. The accumulation of Si by the sorghum plant did not reduce the size and protein content of the host S. graminum nor of the parasitoid L. testaceipes. Silicon induced direct and indirect resistance of sorghum to S. graminum aphid.